HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP DENGAN PERILAKU MENGHADAPI DISMENORE PADA REMAJA PUTRI DI SMK DAYA UTAMA BEKASI TAHUN 2021 - Marini Agustin; Kuni Purwani; Husnul Aulia (Afiat, 2021)
The knowledge possessed by young women about dysmenorrhea is the basis for the formation of behavior to deal with and deal with dysmenorrhea. Good behavior is not only determined by attitudes, beliefs, and traditions, good knowledge will form positive behavior. This study aims to analyze whether there is arelationship between the level of knowledge and attitudes with behavior in dealing with dysmenorrhea in class XI adolescent girls at SMK Daya Utama Bekasi in 2021. The research method used is descriptive correlative. The sampling technique was a saturated sample with a total sample of 50 female students who haddysmenorrhea. The analysis used univariate and bivariate using chi-square with